2002
DOI: 10.1108/14626000210438607
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong learning and SMEs: issues for research and policy

Abstract: Research evidence suggests that SMEs are significantly less likely than larger employers to provide or fund formal training leading to qualifications for employees. The training (or more accurately learning) that does take place in most SMEs tends to be informal, on-the-job and related to short-term business objectives or problems. There are strong arguments to suggest that this type of approach is perfectly rational from the point of view of the small business, but may not produce the optimum level or mix of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 1 publication
2
88
0
2
Order By: Relevance
“…These facets include the deficient amount of empirical research about SMEs regarding how to generate, maintain and transmit innovative knowledge (Johnson, 2002;Nelson, Brunetto, Farr-Wharton, & Ramsay, 2007;Scozzi, et al, 2005). This study is designed to examine the impact of three organisational factors upon the perceived usefulness of workplace social networks and the impact the perceived usefulness has upon the innovative behaviour of SME employees.…”
Section: Introductionmentioning
confidence: 99%
“…These facets include the deficient amount of empirical research about SMEs regarding how to generate, maintain and transmit innovative knowledge (Johnson, 2002;Nelson, Brunetto, Farr-Wharton, & Ramsay, 2007;Scozzi, et al, 2005). This study is designed to examine the impact of three organisational factors upon the perceived usefulness of workplace social networks and the impact the perceived usefulness has upon the innovative behaviour of SME employees.…”
Section: Introductionmentioning
confidence: 99%
“…However, SME employees are perceived by some commentators as a 'disadvantaged' group within the workforce (Devins, Johnson, & Sutherland 2004) because studies in several countries have found that smaller businesses are considerably less likely to provide formal T&D for their employees than larger businesses (Johnson, 2002;Kitching & Blackburn, 2002;Kotey & Folker, 2007;Smith & Billett, 2005;Storey, 2004). This discrepancy is attributable to several factors including the greater barriers to formal T&D faced by SMEs compared to their larger counterparts (Devins et al, 2004;Kitching & Blackburn 2002;Kotey & Folker 2007).…”
Section: Introductionmentioning
confidence: 62%
“…These barriers include the cost of such T&D and the opportunity cost of employees' time when they attend T&D events. Commentators also point out that SME owners/managers are reluctant to invest in external T&D because it usually does not focus on firm-specific problems, priorities and work practices (Gibb 1997;Johnson, 2002;Kitching & Blackburn 2002). In Australia, where 99.7% of businesses are SMEs (Department of Innovation, Industry, Science and Research, 2011), statistical evidence on the level of employer training is mixed, with some evidence suggesting that Australia is a poor performer by international standards in the provision of training (Smith & Billett, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite calls for better approaches to improving small firm management generally (e.g., Down, 1999), there remains a general lack of understanding of the limited uptake of business improvement activities by owner-managers (Jameson, 2000;Johnson, 2002). This is the case even though, as Massey (2004) suggests, training in the small to medium enterprise sector is a huge investment in training by governments around the world.…”
Section: Introductionmentioning
confidence: 90%
“…Indeed, Johnson (2002) argues that small firms are behaving quite rationally in rejecting a strong focus on training activities. For instance, there is a well established chronic fear of staff mobility resulting in efforts to develop staff to be seen as a largely wasted investment (Patton and Marlow, 2002).…”
Section: Attitude Toward Trainingmentioning
confidence: 98%